RNA Binding Protein YTHDF2 Inhibits Synovial Fibroblast Inflammation and Bone Injury in Rheumatoid Arthritis by Reducing the mRNA Stability of IL‐6R - Yan Zhang; Xu‐Qing Cao; Xiao‐Li Ma; Yin‐Yan Guo; Tao Zhang; Li‐Li Wu; Ya‐Shan Yang; Chun‐Fang Hao; Wei‐Li Liu; Jiang‐Tao Guo (Kaohsiung Journal of Medical Sciences)
ABSTRACT This study examined YTHDF2's role in modulating IL‐6R signaling to regulate synovial fibroblast inflammation and bone damage in rheumatoid arthritis (RA). Synovial tissues of RA patients were collected. Human fibroblast‐like synoviocyte (FLS), MH7A cell line, was induced with TNF‐α and transfected. Cell proliferation was assessed using MTT and EdU assays; apoptosis was measured with flow cytometry, and migration and invasion were evaluated through scratch and Transwell assays. Lentiviral vectors designed to overexpress YTHDF2 or IL‐6R were created to study their effects in mice with collagen‐induced arthritis (CIA). Pathological changes of ankle joints in mice were observed, and TNF‐α, IL‐1β, and IL‐6 contents were determined. MMP3 and MMP9 levels were detected by Western blot, while YTHDF2 and IL‐6R were detected by RT‐qPCR and Western blot. The binding relationship between YTHDF2 and IL‐6R was studied. YTHDF2 in synovial tissues of RA patients was down‐regulated. Elevating YTHDF2 inhibited TNF‐α‐induced MH7A cell proliferation, migration, invasion, and pro‐inflammatory factors; Knocking down YTHDF2 showed the opposite effect. Upregulating YTHDF2 improved synovial inflammation and bone damage in CIA mice. IL‐6R in synovial tissues of patients was significantly up‐regulated and negatively correlated with YTHDF2 expression. YTHDF2 reduced IL‐6R mRNA stability in a m6A‐dependent manner. Overexpressing IL‐6R impaired the anti‐proliferating and anti‐inflammatory effect of YTHDF2 on TNF‐α‐induced MH7A cells. In CIA mice, overexpression of IL‐6R reversed the benefits on synovial inflammation and bone injury mediated by up‐regulating YTHDF2. YTHDF2 inhibits inflammation and bone damage in RA synovial fibroblasts by reducing the mRNA stability of IL‐6R.